Quotations for all occasions - Frank, Catherine (Columbia University Press, 2000)
From menopause to moving in, from a first date to losing weight, this ingeniously organized book of quotations fills a gap on everyone's reference shelf. Dividing life's events into those that occur every year, occasionally, or once in a lifetime, Quotations for All Occasions provides memorable comments for each of them, allowing you to find the perfect bon mot for all of life's characteristic passages.